Factors influencing Farmers’ Adaptive capacity to climate change - Swayangsu Sthitaprajna; Dr. Simantini Shasani (Indian Journal of Extension Education, 2025)
The study was carried out in the Kendrapara district of Odisha to assess the adaptive capacity of farmers to climate change with a view to analysing the socio-economic, communication and psychological profile attributes in the year 2024. India’s agrarian economy is at risk from both gradual climatic shifts and sudden extreme weather events, emphasising the need for adaptation and resilience-building strategies. Both purposive and random sampling techniques were followed for the selection of the district, blocks, villages, and respondents, and primary data were collected from 120 respondents through a pre-tested structured interview schedule developed. Five dimensions, namely social capital, physical capital, economic capital, human capital and management capital, were considered to assess the adaptive capacity. (71.6%) of the respondents had a medium level of adaptive capacity, followed by low level (16.67%) and high level (11.67%). Among the independent variables taken, education, scientific orientation, and social participation showed a strong positive correlation with the adaptive capacity. 65% variance towards adaptive capacity was economic motivation, age, education, social participation, annual income, risk preference, farming experience, information source utilisation, extension participation, and scientific orientation.